Performance of oscilene-s, an organic antifungal product against Pyricularia grisea causing blast disease of rice - and S.N. TEWARI*, SUPREET UPADHYAYA, J. BEHERA (Indian Phytopathology, 2012)
Ocimum sanctum steamed aqueous extract was combined with a formulating agent (coded A+) and named Oscilenes, bioassayed under in-vitro condition against Pyricularia grisea causing blast disease of rice. Fungitoxic patterns of importance such as complete inhibition, granulation in cytoplasm, reduction in germ tube length, production of thinner or coiled germ tube in conidial germination and restriction in mycelial growth were registered through various experimentation confirmed the fungitoxic strength of the formulated product. The shelf-life effect on retention of the fungitoxicity of the product was also examined and found superior especially in eight months storage test. In a separate test of the product in green house it was not only found to effectively reduce the foliar blast of rice but also comparable to a Standard synthetic fungicide carbendazim